Estudantes com deficiência intelectual em bandas marciais de escolas regulares: valorização da diversidade - Jovini, Frederico Antônio Dervão (Universidade Federal de São Carlos, 2014)
The School Marching Band is characterized currently as a group of students involved in artistic activities at school. It was developed in schools in the Brazilian military period. It is characterized as a group of students enrolled in artistic activities among them, music and choreography. Such activities provide students with an educational plan that conveys values as discipline, determination, confidence, respect, camaraderie, fellowship and friendship. For these reasons among others, can school bands provide motivating inclusive practice recognition of differences and appreciation of diversity in regular school? The objective of this research was to analyse the participation of students from a percussion band with Intellectual Disabilities (ID) from a special school included in a marching band of a regular school during rehearsals and public performances. This research was under the proposed of a study case, a participant observation was used as the main source of evidence for data collection and the data analysis was a qualitative study using content analysis. A pilot study was conducted aiming to determine the version of the search to be performed helping to collect the data to be tested. The survey was conducted in a school of basic education that has a marching band. Survey participants were: (i) 12 students of the special school of both genders aged 11-12 , (ii) 12 students in a regular school of both genders aged 10 to 21 ( total 22 students), and (iii) a conductor. The criteria used for the sample of the research were: (i) being a student with school age from a special school for ID and participant in the school band for over 12 months, (ii) being a student of school age up to 21years old, being a current student or former one of public regular school participating actively of the school band; and (iii) being the conductor of the chosen school band included in the survey. The data collected were organized into frames for easier viewing and analysis. The results of these analyses could provide the material needed to investigate the effects and implications of the inclusion of students with ID school marching band in the process. The data were compared and analysed and they have shown that the work performed with bands of regular schools is a valuable tool to motivate the value of diversity in regular schools. The participation of students with ID in these artistic activities promotes support and recognition of their differences. Thus, the inclusive practice is effective.
Students with intellectual disabilities in martial bands of regular schools: valuing diversity
Keywords: Bandas marciais e estudantis; Inclusão; Special education; Marching band; Inclusion; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL